Ceramic tile and preparation method thereof
Through hydrothermal carbonization reaction and the addition of manganese nitrate, modified kaolin and waste residue materials are prepared as effective components, which solves the problems of fragile texture and poor thermal insulation performance of traditional ceramic tiles, and achieves high-strength and low thermal conductivity of ceramic tiles, and effectively utilizes waste residue materials and reduces environmental pollution.
Patent Information
- Application Number
- CN202510031652.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-09
AI Technical Summary
Traditional ceramic tiles have fragile texture, weak mechanical properties, and poor thermal insulation properties, making them difficult to meet the demand for high-strength and low-thermal conductivity ceramic tiles in modern buildings.
The cellulose is carbonized on the surface of kaolin through hydrothermal carbonization reaction, reducing the thermal conductivity of ceramic tiles, and adding manganese nitrate during the modification process to improve the hybridization degree of the kaolin surface structure and improve the strength and thermal insulation properties of ceramic tiles.
It significantly improves the thermal insulation performance and strength of ceramic tiles, improves the overall performance and stability of the material, and at the same time realizes the efficient utilization of waste slag materials, reducing environmental pollution.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of inorganic non-metallic ceramic materials, and in particular to a ceramic tile and a preparation method thereof. Background Art
[0002] As an important building material, ceramic tiles play a vital role in the construction industry. They not only have beautiful appearance, but also have excellent durability and wind and rain resistance. With the advancement of technology and the continuous changes in the market, the performance and quality requirements of ceramic tiles are getting higher and higher. Therefore, it is particularly important to develop a new type of ceramic tile and its preparation method.
[0003] Traditional ceramic tiles are made of natural inorganic materials such as kaolin and linderaite through molding, drying and firing. However, ceramic tiles have also exposed some defects during use, which affect their use effect and application range, such as: traditional ceramic tiles are brittle, have weak mechanical properties, and have poor thermal insulation properties. Therefore, it is urgent to develop a ceramic tile with high strength and low thermal conductivity. Summary of the invention
[0004] In order to overcome the shortcomings of the prior art, the primary purpose of the present invention is to provide a ceramic tile. The present invention carbonizes cellulose on the surface of kaolin through a hydrothermal carbonization reaction, thereby reducing the thermal conductivity of the ceramic tile and improving the thermal insulation of the material; then manganese nitrate is added during the modification process to further increase the hybridization degree of the kaolin surface structure, improve the strength of the ceramic tile, and help improve the overall performance and stability of the material.
[0005] A ceramic tile comprises the following raw materials in parts by weight: 40-50 parts of waste residue, 1-5 parts of barium carbonate, 5-8 parts of feldspar powder, 0.5-3 parts of zinc oxide, 2-7 parts of colorant, 15-20 parts of modified kaolin, and 1-5 parts of water; the waste residue comes from a limestone mine and is limestone beneficiation waste residue;
[0006] The preparation process of the modified kaolin is as follows:
[0007] (1) adding kaolin to deionized water, then adding octadecyl bis(hydroxyethyl)methylammonium chloride, stirring at room temperature for a period of time, filtering and drying to obtain pretreated kaolin;
[0008] (2) Add the kaolin pretreated in step (1) into deionized water, then add cellulose and manganese nitrate, heat to react, and after the reaction is completed, filter, wash and dry to obtain modified kaolin.
[0009] Furthermore, the mass ratio of kaolin, octadecyl bis(hydroxyethyl)methylammonium chloride and water in step (1) is 1:(0.4-0.6):(10-15).
[0010] Furthermore, the stirring time in step (1) is 7-10 hours.
[0011] Furthermore, the mass ratio of the pretreated kaolin, cellulose and manganese nitrate in step (2) is 1:(0.3-0.5):(0.05-0.2).
[0012] Furthermore, the heating temperature in step (2) is 220-260° C. and the heating time is 8-10 h.
[0013] Furthermore, the particle size of the waste slag material is ≤5mm. Another object of the present invention is to provide a method for preparing ceramic tiles. The present invention uses limestone ore dressing waste slag as an effective component to prepare ceramic tiles. The waste slag material of the present invention is limestone ore dressing waste slag, which realizes the best use of materials and waste utilization, and effectively improves the resource utilization rate of ore dressing waste slag.
[0014] The purpose of the present invention is achieved through the following technical solutions:
[0015] A method for preparing a ceramic tile comprises the following steps:
[0016] a. Weigh the waste material, barium carbonate, feldspar powder, zinc oxide, colorant, and modified kaolin in the above parts by weight and add them to water, stir and mix to obtain a slurry;
[0017] b. Inject the slurry into the mold, let it stand for molding, dry and sinter.
[0018] Furthermore, the sintering in step b comprises the following steps:
[0019] First sinter at 500-700℃ for 0.5-1h; then sinter at 1000-1200℃ for 2-3h.
[0020] Furthermore, the static molding time in step b is 22-28 hours; the drying temperature is 90-110° C. and the drying time is 80-120 minutes.
[0021] The present invention has the following effects compared with the prior art:
[0022] 1. The present invention provides a ceramic tile, which creatively introduces modified kaolin, waste residue and other components, wherein the modified kaolin is first pre-treated to improve the dispersibility of kaolin in water and provide favorable surface conditions for subsequent reactions. The present invention carbonizes cellulose on the surface of kaolin through a hydrothermal carbonization reaction, thereby reducing the thermal conductivity of the ceramic tile and improving the thermal insulation of the material; then, manganese nitrate is added during the modification process, further increasing the hybridization degree of the kaolin surface structure, improving the strength of the ceramic tile, and helping to improve the overall performance and stability of the material.
[0023] 2. The present invention provides a method for preparing ceramic tiles, which uses waste slag as an effective component to prepare ceramic tiles. The waste slag described in the present invention is limestone ore dressing waste slag, which achieves full use of resources and waste utilization, effectively improves the resource utilization rate of ore dressing waste slag, and reduces environmental pollution. DETAILED DESCRIPTION
[0024] The present invention will be described in further detail below in conjunction with the examples, but the embodiments of the present invention are not limited thereto. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. The test methods for which specific experimental conditions are not specified in the following examples are usually carried out according to conventional experimental conditions or according to the experimental conditions recommended by the manufacturer. Unless otherwise specified, the reagents and raw materials used in the present invention can be obtained commercially.
[0025] The particle size of the waste slag material in the present invention is ≤5 mm, and the waste slag material comes from a limestone mine and is limestone beneficiation waste slag.
[0026] Example 1
[0027] A ceramic tile is composed of the following raw materials in parts by weight: 45 parts of waste residue, 3 parts of barium carbonate, 7 parts of potassium feldspar powder, 2 parts of zinc oxide, 5 parts of cobalt black material, 18 parts of modified kaolin, and 3 parts of water;
[0028] The preparation process of the modified kaolin is as follows:
[0029] (1) adding kaolin to deionized water, and then adding octadecyl bis(hydroxyethyl)methyl ammonium chloride, wherein the mass ratio of kaolin, octadecyl bis(hydroxyethyl)methyl ammonium chloride and water is 1:0.5:12, stirring at room temperature for 8 hours, filtering and drying to obtain pretreated kaolin;
[0030] (2) Add the kaolin pretreated in step (1) into deionized water, and then add cellulose and manganese nitrate, wherein the mass ratio of the pretreated kaolin, cellulose and manganese nitrate is 1:0.4:0.1; react at 240° C. for 9 hours. After the reaction is completed, filter, wash and dry to obtain modified kaolin.
[0031] A method for preparing a ceramic tile comprises the following steps:
[0032] (1) Weigh the waste slag material, barium carbonate, potassium feldspar powder, zinc oxide, and cobalt black material according to the above weight parts, add them into water, and stir and mix to obtain a slurry.
[0033] (2) Inject the slurry into the model, let it stand at room temperature for 24 hours, and then dry it at 100°C for 100 minutes; first heat it to 500°C at a heating rate of 2°C / min and keep it at this temperature for 1 hour; then heat it to 1100°C at a heating rate of 0.5°C / min and keep it at this temperature for 2 hours, and then cool it down.
[0034] Example 2
[0035] A ceramic tile is composed of the following raw materials in parts by weight: 40 parts of waste residue, 1 part of barium carbonate, 5 parts of sodium feldspar powder, 0.5 parts of zinc oxide, 2 parts of cobalt black material, 15 parts of modified kaolin, and 1 part of water;
[0036] The preparation process of the modified kaolin is as follows:
[0037] (1) adding kaolin to deionized water, and then adding octadecyl bis(hydroxyethyl)methyl ammonium chloride, wherein the mass ratio of kaolin, octadecyl bis(hydroxyethyl)methyl ammonium chloride and water is 1:0.4:10, stirring at room temperature for 7 hours, filtering and drying to obtain pretreated kaolin;
[0038] (2) Add the kaolin pretreated in step (1) into deionized water, and then add cellulose and manganese nitrate, wherein the mass ratio of the pretreated kaolin, cellulose and manganese nitrate is 1:0.3:0.05; react at 220° C. for 8 h. After the reaction is completed, filter, wash and dry to obtain modified kaolin.
[0039] A method for preparing a ceramic tile comprises the following steps:
[0040] (1) Weigh the waste slag material, barium carbonate, sodium feldspar powder, zinc oxide, cobalt black material, and modified kaolin according to the above weight parts, add them into water, stir and mix to obtain a slurry,
[0041] (2) The slurry was injected into the model, allowed to stand at room temperature for 22 h, and then dried at 110 °C for 80 min; the temperature was first raised to 600 °C at a heating rate of 2 °C / min and the holding time was 0.5 h; the temperature was then raised to 1000 °C at a heating rate of 0.5 °C / min and the holding time was 3 h, and the product was cooled.
[0042] Example 3
[0043] A ceramic tile is composed of the following raw materials in parts by weight: 50 parts of waste residue, 5 parts of barium carbonate, 8 parts of potassium feldspar powder, 3 parts of zinc oxide, 7 parts of cobalt black material, 20 parts of modified kaolin, and 5 parts of water;
[0044] The preparation process of the modified kaolin is as follows:
[0045] (1) adding kaolin to deionized water, and then adding octadecyl bis(hydroxyethyl)methyl ammonium chloride, wherein the mass ratio of kaolin, octadecyl bis(hydroxyethyl)methyl ammonium chloride and water is 1:0.6:15, stirring at room temperature for 10 hours, filtering and drying to obtain pretreated kaolin;
[0046] (2) Add the kaolin pretreated in step (1) into deionized water, and then add cellulose and manganese nitrate, wherein the mass ratio of the pretreated kaolin, cellulose and manganese nitrate is 1:0.5:0.2; react at 260° C. for 10 hours. After the reaction is completed, filter, wash and dry to obtain modified kaolin.
[0047] A method for preparing a ceramic tile comprises the following steps:
[0048] (1) Weigh the waste residue, barium carbonate, potassium feldspar powder, zinc oxide, cobalt black material and modified kaolin according to the above weight parts, add them into water, stir and mix to obtain slurry,
[0049] (2) The slurry was injected into the model, allowed to stand at room temperature for 28 h, and then dried at 90 °C for 120 min; the temperature was first raised to 700 °C at a heating rate of 2 °C / min and kept at this temperature for 1 h; the temperature was then raised to 1200 °C at a heating rate of 0.5 °C / min and kept at this temperature for 2.5 h, and the product was cooled.
[0050] Comparative Example 1
[0051] This comparative example 1 provides a ceramic tile, which differs from example 1 in that the modified kaolin is replaced with kaolin.
[0052] This comparative example 1 also provides a method for preparing a ceramic tile, and the specific steps are the same as those in Example 1.
[0053] Comparative Example 2
[0054] This comparative example 2 provides a ceramic tile, which differs from the example 1 in that step (1) is retained and step (2) is omitted during the preparation of the modified kaolin.
[0055] This comparative example 2 also provides a method for preparing a ceramic tile, and the specific steps are the same as those of example 1.
[0056] Comparative Example 3
[0057] Comparative Example 3 provides a ceramic tile, which differs from Example 1 in that step (1) is retained in the preparation process of the modified kaolin, and only the addition of manganese nitrate is omitted in step (2).
[0058] This comparative example 3 also provides a method for preparing a ceramic tile, and the specific steps are the same as those of example 1.
[0059] Comparative Example 4
[0060] This comparative example 4 provides a ceramic tile, which is different from the example 1 in that the modified kaolin is replaced with kaolin and cellulose, wherein the amount of kaolin and cellulose used is the same as that in the modified kaolin described in the example 1.
[0061] This comparative example 4 also provides a method for preparing a ceramic tile, and the specific steps are the same as those in Example 1.
[0062] Test Example 1
[0063] In order to characterize the ceramic tiles of Examples 1-3 and Comparative Examples 1-4 of the present invention, the following performance tests were performed:
[0064] (1) Thermal conductivity test: The thermal conductivity of each group of samples in Examples 1-3 and Comparative Examples 1-4 was tested by the hot wire method. Each group was tested three times and the average value was taken as the final test result. The experimental results are shown in Table 1.
[0065] (2) Flexural strength test: The flexural strength of each group of samples of Examples 1-3 and Comparative Examples 1-4 was tested on a universal mechanical material testing machine using a three-point bending method. The experimental results are shown in Table 2.
[0066] Table 1
[0067]
[0068] It can be seen from the test results in Table 1 that the thermal conductivity of the ceramic tiles of Examples 1-3 of the present invention is significantly lower than that of Comparative Examples 1-3. Compared with Example 1, Comparative Example 1 replaces the modified kaolin with kaolin, and Comparative Example 2 omits step (2), that is, the modified kaolin is replaced with pretreated kaolin. The thermal conductivity of both is at a relatively high level. In the process of preparing modified kaolin, Comparative Example 3 retains step (1), and only omits the addition of manganese nitric acid in step (2). Comparative Example 4 replaces the modified kaolin with a physical composite of kaolin and cellulose. The thermal conductivity of Comparative Example 3 is significantly lower than that of Comparative Example 4, but the thermal conductivity is higher than that of Example 1. This may be because the modified kaolin carbonizes cellulose on the surface of kaolin through a hydrothermal carbonization reaction during the preparation process, which can effectively reduce the thermal conductivity efficiency of the material and improve the thermal insulation performance of the ceramic tiles.
[0069] Table 2
[0070]
[0071] It can be seen from the data in Table 2 that the ceramic tiles obtained in Examples 1-3 of the present invention all have good flexural strength, all maintained above 26MPa, which is significantly higher than Comparative Examples 1-4. Among them, Comparative Example 1 replaces the modified kaolin with kaolin, and the flexural strength of this group is the worst, followed by Comparative Example 2. Comparative Example 3 is slightly higher than Comparative Example 4, indicating that carbonizing cellulose on the surface of kaolin through a hydrothermal carbonization reaction can further improve the strength of the ceramic tiles to a certain extent. Compared with Example 1, Comparative Example 3 omits the addition of manganese nitrate in the process of preparing modified kaolin, and the flexural strength drops to 20.41MPa. This result shows that by adding manganese nitrate during the modification process, the hybridization degree of the kaolin surface structure can be further improved, thereby improving the strength and overall performance of the ceramic tiles.
[0072] In summary, the present invention uses modified kaolin and waste residue as effective components to prepare ceramic tiles, which can not only significantly improve the thermal insulation performance, strength and overall performance of the material, but also make the best use of waste, effectively improve the resource utilization rate of mineral processing waste residue, and reduce environmental pollution. It proves that the modified kaolin has broad prospects in applications such as ceramic tiles.
[0073] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.
Claims
1. A ceramic tile, characterized in that: The invention comprises the following raw materials in parts by weight: 40-50 parts of waste residue, 1-5 parts of barium carbonate, 5-8 parts of feldspar powder, 0.5-3 parts of zinc oxide, 2-7 parts of colorant, 15-20 parts of modified kaolin and 1-5 parts of water; the waste residue comes from a limestone mine and is limestone beneficiation waste residue; The preparation process of the modified kaolin is as follows: (1) adding kaolin to deionized water, then adding octadecyl bis(hydroxyethyl)methylammonium chloride, stirring at room temperature for a period of time, filtering and drying to obtain pretreated kaolin; (2) Add the kaolin pretreated in step (1) into deionized water, then add cellulose and manganese nitrate, heat to react, and after the reaction is completed, filter, wash and dry to obtain modified kaolin.
2. The ceramic tile according to claim 1, characterized in that: The mass ratio of kaolin, octadecyl bis(hydroxyethyl)methylammonium chloride and water in step (1) is 1:(0.4-0.6):(10-15).
3. The ceramic tile according to claim 1, characterized in that: The stirring time in step (1) is 7-10 hours.
4. The ceramic tile according to claim 1, characterized in that: The mass ratio of the pretreated kaolin, cellulose and manganese nitrate in step (2) is 1:(0.3-0.5):(0.05-0.2).
5. The ceramic tile according to claim 1, characterized in that: The heating temperature in step (2) is 220-260° C. and the heating time is 8-10 h.
6. The ceramic tile according to claim 1, characterized in that: The particle size of the waste residue is ≤5mm.
7. The method for preparing a ceramic tile according to claim 1, characterized in that: The steps include: a. Weigh the waste material, barium carbonate, feldspar powder, zinc oxide, colorant, and modified kaolin in the above parts by weight and add them to water, stir and mix to obtain a slurry; b. Inject the slurry into the mold, let it stand for molding, dry and sinter.
8. The method for preparing a ceramic tile according to claim 7, characterized in that: The sintering in step b comprises the following steps: First sinter at 500-700℃ for 0.5-1h; then sinter at 1000-1200℃ for 2-3h.
9. The method for preparing a ceramic tile according to claim 7, characterized in that: The static forming time of step b is 22-28 hours; the drying temperature is 90-110° C. and the drying time is 80-120 minutes.
Citation Information
Patent Citations
Process for making petuntse by using waste ceramic
CN107903029A